Обезбеђење трошкова спора у арбитражи по правилима МТК и ИКСИД-а - Stanivuković, Maja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
У овом раду смо показали да се захтев за одређивање обезбеђења за трошкове спора све чешће јавља у међународној арбитражи по правилима МТК и ИКСИД-а, да арбитражни судови ретко одређују ову меру и да су услови за њено одређивање још увек релативно недефинисани. Чини се да је праг који тужени мора да пређе да би убедио арбитражни суд да постоје изузетне околности које оправдавају одређивање ове мере изузетно висок. Сама чињеница да је тужилац инсолвентан није довољна да би таква одлука била донета. The Article is about security for costs in international arbitration under the ICC and ICSID Rules. It first treats the questions who is entitled to submit such a request, what kind of costs are secured, whether the tribunal has authority to order such measure, and the basis of such authority. This is followed by the discussion of the conditions for ordering the measure and the reasons that speak against it. Among various exceptional circumstances justifying the measure that are mentioned in arbitral practice, the following are given some attention: manifest insolvency or bankruptcy of the claimant, SPV ас claimant, third party financing of the claim, change of circumstances, respondent is not a signatory to the arbitration agreement, probability that respondent will be awarded costs. Reasons speaking against the measure mentioned in the cases are the following: consent to the risk of insolvent claimant, access to arbitral justice, equity, respondent’s bad faith, untimeliness of the request. Finally, certain questions of procedure are discussed such as burden of proof and consequences of claimant’s non-compliance with the ordered security. The author concludes that arbitrators in ICC and ICSID arbitration are still reluctant to order security for costs although such requests by respondents have become more frequent. The threshold respondent must reach to convince the tribunal that there are exceptional circumstances justifying the measure is high. The fact that claimant is insolvent alone does not suffice for the success of such request.